Development and successful real‐world use of a transfer DNA technique to identify species involved in shark bite incidents. Issue 6 (19th July 2021) - Kraft, Derek; Meyer, Lauren; Webb, Maryann; Scidmore‐Rossing, Kaylee; Huveneers, Charlie; Clua, Eric; Meyer, Carl
Abstract: Identifying the species involved in shark bite incidents is an ongoing challenge but is important to mitigate risk. We developed a sampling protocol to identify shark species from DNA transferred to inanimate objects during bite incidents. To develop and refine the technique, we swabbed shark bite impressions on surfboards and wetsuit neoprene collected under semicontrolled conditions. Methods were tested experimentally and then successfully used to identify the species involved in a real‐world shark bite incident. Thirty‐two of 33 bite impressions yielded sufficient DNA sequences for species identification, producing barcodes from five test species, including dusky, Galapagos, bull, tiger, and white shark. The latter three species collectively account for a majority of shark bites worldwide. Our method successfully identified the species ( Galeocerdo cuvier ) responsible for a fatal shark bite on December 8th, 2020 on the island of Maui, from swab samples collected from the victim's surfboard 49 h after the bite incident. Our experimental results demonstrate that shark species can be accurately identified from transfer DNA recovered from bite impressions on surfboards and wetsuit neoprene. The successful use of our method in the real‐world incident shows great potential for the practicality of this tool. We recommend DNA swabbing as a routine part of the forensic analysis of shark bites to help identify the species involved in human‐shark interactions.